Condensation Enhancement on Hydrophobic Surfaces Using Electrophoretic Method and Hybrid Paint Coating. Issue 18 (11th October 2021) - Najafpour, Sahand; Moosavi, Ali; Najafkhani, Hosein
Abstract: Condensation heat transfer on stainless steel tube utilizing superhydrophobic coatings was investigated. The electrophoretic deposition and spraying methods were employed to coat the tubes' outer surface. The mixture that was synthesized for spray coating was a hybrid paint. It incorporated polyurethane matrix and a colloidal suspension containing organic nanoparticles. The hybrid paint had a proper adhesion to the substrate which caused more durability compared to the electrophoretic coating. The agglomeration of nanoparticles in the hybrid paint caused the formation of particles with larger size compared to the particles in the electrophoretic coating. Consequently, contact angle hysteresis over electrophoretic coating was much lesser than spraying method. Dropwise condensation regime was observed over both the coatings as a result of hydrophobicity. Nonetheless, the condensation heat flux declined over the hybrid paint at high subcooling temperatures due to transition to the flooding condensation regime. This was due to the accumulation of ultra-small droplets as a result of high nucleation sites. The continuation of droplets sweeping was hindered by sticking to the substrate. The dropwise condensation was maintained over the electrophoretic coating and the transition to the film-wise condensation happened at larger wall subcooling temperature. The ability of the electrophoretic coating in shedding droplets efficiently was caused by higher hydrophobicity, high roughness density, and minimum droplet pinning.